Белоснежка и золотое колечко - Прокофьева Софья Леонидовна (Волшебный фонарик, 1999)
Экземпляры: ДБ (20120709) / Инвентарный номер: 40894zzzzz / Цена: 50.60 / Сис.шифр: 84(2) / Авт.знак: П 80 / ГРНТИ: 17.82.93 / ББК: 84(2=Рус)